2014
DOI: 10.1007/s12031-014-0395-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxic Properties of a Cyclopamine Glucuronide Prodrug in Rat Glioblastoma Cells and Tumors

Abstract: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor. Activation of the developmental hedgehog (Hh) pathway is observed in GBM, particularly in the so-called glioma stem cells (GSCs). An inhibitor of this pathway is the steroidal alkaloid cyclopamine, an antagonist of the Hh coreceptor Smoothened (SMO). To limit the toxicity of cyclopamine toward Hh-dependent non-tumor cells, our group previously reported the synthesis of a prodrug (called 1b), designed to deliver cyclopamine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The pivotal roles of this signaling pathway in maintaining the stemness of tissue stem cells and in regulating the tissue homeostasis and cell fate along the lifespan raise concerns for safety of Wnt-based anticancer strategies despite the potential of Wnt signaling targeting for cancer stem cell elimination 90,91 and metastasis suppression, discouraging their development. Preclinical studies 91 and phase 1 clinical trials 92 suggested that PRI-724 is relatively well-tolerated, and the drug is currently in phase 2 trials combined with chemotherapy drugs and the angiogenesis inhibitor bevacizumab (NIH trial IDs 3C-13-3, NCI-2015-00436, and NCT02413853).…”
Section: Antimetastatic Potential Of Wnt and Hedgehog Targetingmentioning
confidence: 99%
“…The pivotal roles of this signaling pathway in maintaining the stemness of tissue stem cells and in regulating the tissue homeostasis and cell fate along the lifespan raise concerns for safety of Wnt-based anticancer strategies despite the potential of Wnt signaling targeting for cancer stem cell elimination 90,91 and metastasis suppression, discouraging their development. Preclinical studies 91 and phase 1 clinical trials 92 suggested that PRI-724 is relatively well-tolerated, and the drug is currently in phase 2 trials combined with chemotherapy drugs and the angiogenesis inhibitor bevacizumab (NIH trial IDs 3C-13-3, NCI-2015-00436, and NCT02413853).…”
Section: Antimetastatic Potential Of Wnt and Hedgehog Targetingmentioning
confidence: 99%
“…The protocol of RT-qPCR was carried out with the LightCycler System (Roche Molecular Biochemicals) by using the « SYBR Premix Ex Taq kit» (Takara) as previously described [36]. GAPDH mRNA levels were used to normalize the mRNA levels between samples.…”
Section: Real-time Rt-pcr and Quantificationmentioning
confidence: 99%
“…A glucuronide prodrug of monomethylauristatin E (MMAE-glu) [25][26][27][28][29][30][31][32] was chosen to perform this study [33,34]. Indeed, MMAE is a potent antimitotic agent currently employed in human for the treatment of lymphomas under the form of the brentuximab vedotin, an antibody-drug conjugate that reached the market in 2011 [35].…”
Section: Resultsmentioning
confidence: 99%